2019
DOI: 10.1016/j.matlet.2018.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Egg shell membrane template stabilises formation of β-NiMoO4 nanowires and enhances hybrid supercapacitor behaviour

Abstract: Adding an eggshell membrane (ESM) template to the solution combustion synthesis of NiMoO 4 resulted in the formation of -NiMoO 4 under mild conditions. It is postulated that the unique nature of the ESM template results in interactions that stabilise this difficult to synthesise form of NiMoO 4 .The ESM template led to -NiMoO 4 particles that were nano-wire like in shape and arranged in an open weave structure that significantly enhanced the mesoporosity and conductance of the material. The specific capacita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Compared with carbonaceous materials, TMOs can store charges at the electrode surface via faradic reactions. TMOs have the advantage of exhibiting a higher specific capacitance, ensuring a high energy density. Among all the previously reported oxides, manganese oxides (Mn x O y ) and nickel oxides (Ni x O y ) gained tremendous attention for supercapacitor application due to their several benefits, including their high theoretical capacity (∼1360 and ∼2584 F/g for manganese and nickel oxides, respectively), ,, abundancy, cost-efficiency, low toxicity, and multi-oxidation states that ensure an efficient redox charge transfer and enhancing pseudocapacitive behavior. Mn x O y also provides a wide operating voltage window in neutral aqueous electrolytes. ,,,, However, similar to other metal oxides, there are some drawbacks that limit their efficient use in supercapacitors, including agglomeration of the particles that limits the available surface active sites and increases the resistivity, poor mechanical stability, intrinsic low electrical conductivity, and the poor long-term cycling stability. ,,,, To overcome these limitations, Kolathodi et al reported beaded manganese oxide (Mn 2 O 3 ) nanofibers prepared via the surfactant-free electrospinning method, which revealed a capacitance of 358 F/g at 0.5 A/g.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with carbonaceous materials, TMOs can store charges at the electrode surface via faradic reactions. TMOs have the advantage of exhibiting a higher specific capacitance, ensuring a high energy density. Among all the previously reported oxides, manganese oxides (Mn x O y ) and nickel oxides (Ni x O y ) gained tremendous attention for supercapacitor application due to their several benefits, including their high theoretical capacity (∼1360 and ∼2584 F/g for manganese and nickel oxides, respectively), ,, abundancy, cost-efficiency, low toxicity, and multi-oxidation states that ensure an efficient redox charge transfer and enhancing pseudocapacitive behavior. Mn x O y also provides a wide operating voltage window in neutral aqueous electrolytes. ,,,, However, similar to other metal oxides, there are some drawbacks that limit their efficient use in supercapacitors, including agglomeration of the particles that limits the available surface active sites and increases the resistivity, poor mechanical stability, intrinsic low electrical conductivity, and the poor long-term cycling stability. ,,,, To overcome these limitations, Kolathodi et al reported beaded manganese oxide (Mn 2 O 3 ) nanofibers prepared via the surfactant-free electrospinning method, which revealed a capacitance of 358 F/g at 0.5 A/g.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 a shows the CV curves of the Ni(OH) 2 electrode for various scan rates within the potential window range of 0 to 0.5 V versus SCE. All CV curves exhibit a pair of redox peaks caused by the faradaic reaction Ni(OH) 2 + OH − ⇄ NiOOH + H 2 O + e − [ 31 , 34 ], implying the battery-type materials of the Ni(OH) 2 electrode [ 35 , 36 , 37 , 38 ]. As the scan rate increases, the anodic and cathodic peaks shift toward higher and lower potentials, respectively, without a significant change in the shape of the CV profiles, revealing that the Ni(OH) 2 electrode enables rapid redox reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the redox reaction of the Fe-S bond in erdite is subordinate in comparison with the hydrolysis of erdite. MnS is similarly hydrolysed, and the Mn 2+ obtained is oxidised to MnOOH in the presence of dissolved oxygen 51 , which oxidises HS − at ambient condition (Fig. 10, step 2) 45 .
Figure 10Illustration of TC adsorption by erdite particles.
…”
Section: Resultsmentioning
confidence: 99%